PENERAPAN PEACE EDUCATION DALAM KONTEKS NEGARA KONFLIK: SYSTEMATIC LITERATURE REVIEW - Labibatussolihah Labibatussolihah; Nour Muhammad Adriani (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
Historical trauma commonly occurs in countries that have experienced prolonged conflicto, such as civil war, genocide, and rule by authoritarian regimes. This trauma forms a collective memory of the wounds that occurred, resulting in prejudice, stereotypes, and intergroup tensions that lead citizens to an identity crisis. The process of healing these inherited psychological wounds requires efforts to reconstruct their social, political, and moral order. In this context, peace education is a primary approach to instilling the values ​​of tolerance, empathy, reconciliation, and social justice as the foundation for forming global citizenship oriented towards positive actions for the realization of a peaceful society. This study uses a Systematic Literature Review method on the Scopus database from 2020-2025, applying the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) using the keyword